2014
DOI: 10.3892/ol.2014.2422
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of phosphodiesterase 4D inhibits nasopharyngeal carcinoma proliferation via the epidermal growth factor receptor signaling pathway

Abstract: Phosphodiesterase 4D (PDE4D) is a subtype of metallohydrolases, and it has been reported that PDE4D functions as a proliferation promoting factor in certain types of cancer, including head and neck cancer. The present study first investigated the function of PDE4D in nasopharyngeal carcinoma (NPC). Western blot analysis was applied to detect PDE4D expression in NPC samples and cells. A lentiviral infection technique was used to stabilize the knockdown of PDE4D, which was subsequently examined in vitro and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the present study, PDE4D silencing attenuated migration and invasion abilities of PDAC cells and decreased β-catenin level simultaneously. Previous studies have reported that knockdown of PDE4D resulted in EGFR/PI3K/AKT signaling inactivation in nasopharyngeal carcinoma cells 37. And EGF/AKT could contribute to phosphorylation of β-catenin and increased its protein level in cancer cells, therefore, enhanced β-catenin downstream transcriptional activity 38, 39.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, PDE4D silencing attenuated migration and invasion abilities of PDAC cells and decreased β-catenin level simultaneously. Previous studies have reported that knockdown of PDE4D resulted in EGFR/PI3K/AKT signaling inactivation in nasopharyngeal carcinoma cells 37. And EGF/AKT could contribute to phosphorylation of β-catenin and increased its protein level in cancer cells, therefore, enhanced β-catenin downstream transcriptional activity 38, 39.…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, both PDE4D (phosphodiesterase 4D) and SERP2 (stress-associated endoplasmic reticulum protein family member 2) are associated with tumors [ 62 , 63 ]. Among them, PDE4D has been reported to act as a proliferation promoter in several different tumors [ 64 66 ], and mutations in SERP2 are associated with leukemia [ 67 ]. In our study, both the 2 loci were connected to Cer(d18:0/12:0), but further studies are needed to explore the specific relationship between the occurrence of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that PDE4D may function in cancer via different pathways, including the EGFR/phosphoinositide 3-kinase/protein kinase B signalling pathway, MAPK pathway and Hedgehog pathway ( 66 68 ). However, further exploration is required to clarify the potential molecular mechanisms of PDE4D in NSCLC.…”
Section: Discussionmentioning
confidence: 99%